The integration of GC–MS and LC–MS to assay the metabolomics profiling in Panax ginseng and Panax quinquefolius reveals a tissue- and species-specific connectivity of primary metabolites and ginsenosides accumulation - Liu, Jia; Liu, Yang; Wang, Yu; Abozeid, Ann; Zu, Yuan-Gang; Tang, Zhong-Hua (Journal of pharmaceutical and biomedical analysis, 2017)
[Display omitted] •Tissue-specific profiling of primary and secondary metabolites in two different species of ginseng by using GC- and LC-MS.•Revealed a complex consecutive coordination of primary and secondary metabolism and corresponding pathways.•149 primary metabolites and 10 ginsenosides were identified from tissues-specific in P. ginseng and P. quinquefolius.•To investigate the contribution of tissue-specific C and N metabolism to the biosynthesis of ginsenosides.•Ginsenosides was dependent on main and lateral root energy metabolism and independent of leaf and petiole photosynthesis. The traditional medicine Ginseng mainly including Panax ginseng and Panax quinquefolius is the most widely consumed herbal product in the world. Despite the extensive investigation of biosynthetic pathway of the active compounds ginsenosides, our current understanding of the metabolic interlink between ginsenosides synthesis and primary metabolism at the whole-plant level. In this study, the tissue-specific profiling of primary and the secondary metabolites in two different species of ginseng were investigated by gas chromatography- and liquid chromatography coupled to mass spectrometry. A complex continuous coordination of primary- and secondary-metabolic network was modulated by tissues and species factors during growth. The results showed that altogether 149 primary compounds and 10 ginsenosides were identified from main roots, lateral roots, stems, petioles and leaves in P. ginseng and P. quinquefolius. The partial least squares-discriminate analysis (PLS-DA) revealed obvious compounds distinction among tissue-specific districts relative to species. To survey the dedication of carbon and nitrogen metabolism in different tissues to the accumulation of ginsenosides, we inspected the tissue-specific metabolic changes. Our study testified that the ginsenosides content was dependent on main roots and lateral roots energy metabolism, whereas independent of leaves and petiole photosynthesis during ginsenosides accumulation. When tow species were compared, the results indicated that high rates of C assimilation to C accumulation are closely associated with ginsenosides accumulation in P. ginseng main roots and P. quinquefolius lateral roots, respectively. Taken together, our results suggest that tissue-specific metabolites profiling dynamically changed in process of ginsenosides biosynthesis, which may offer a new train of thoughts to the mechanisms of the ginsenosides biosynthesis at the metabolite level.